2022
DOI: 10.48550/arxiv.2202.12262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Omnipresence of Spurious Local Minima in Certain Neural Network Training Problems

Abstract: We study the loss landscape of training problems for deep artificial neural networks with a one-dimensional real output whose activation functions contain an affine segment and whose hidden layers have width at least two. It is shown that such problems possess a continuum of spurious (i.e., not globally optimal) local minima for all target functions that are not affine. In contrast to previous works, our analysis covers all sampling and parameterization regimes, general differentiable loss functions, arbitrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…A good literature review regarding the loss landscape in neural network training can be found in [EMWW20]. For statements about the existence of non-optimal local minima in the training of (shallow) networks we refer the reader to [SCP16, SS18, VBB19] and [CK22].…”
Section: Introductionmentioning
confidence: 99%
“…A good literature review regarding the loss landscape in neural network training can be found in [EMWW20]. For statements about the existence of non-optimal local minima in the training of (shallow) networks we refer the reader to [SCP16, SS18, VBB19] and [CK22].…”
Section: Introductionmentioning
confidence: 99%